The Impact of Unemployment and Human Development Index on Poverty in Gorontalo Province 2008-2017 - Lian A Yusuf; Sri Indriyani Dai (Jambura Equilibrium Journal, 2020)
This research aims to analyze the impact of unemployment rate and human development index on poverty in Regecies and City in Gorontalo Province. This research uses Panel Data Regression analysis with fixed effect model (FEM). This research uses regional datasets from the Registration Management Information System (SIMREG) and datasets from Central Statistics Bureau (BPS) during 2008-2017. Main findings of this research indicates that (i) unemployment rate has positive but insignificant impact on poverty rate; (ii) human development index has positive and significant impact on poverty rate. Keywords: Unemployment Rate; Human Development Index (HDI); Poverty.